The complete web developer course 2.0 - Percival, Rob (Packt Publishing, 2018)
"This course will take you on a journey where you will learn to build websites and mobile apps using HTML, CSS, JavaScript, PHP, Python, MySQL & more. The course starts with the fundamentals and shows tips to work quickly and efficiently with web technologies like HTML5, CSS3 and Python. You will learn to build your own responsive websites using more advanced techniques such as iQuery PHP 7, MySQL 5 and Twitter Bootstrap and to develop blogs and eCommerce sites with Wordpress, and learn smart ways to add dynamic content, using APls to connect to sites such as Google Maps and Facebook."--Resource description page